2021
DOI: 10.48550/arxiv.2110.05495
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Compact Object Modeling in the Globular Cluster 47 Tucanae

Claire S. Ye,
Kyle Kremer,
Carl L. Rodriguez
et al.

Abstract: The globular cluster 47 Tucanae (47 Tuc) is one of the most massive star clusters in the Milky Way and is exceptionally rich in exotic stellar populations. For several decades it has been a favorite target of observers, and yet it is computationally very challenging to model because of its large number of stars (N 10 6 ) and high density. Here we present detailed and self-consistent 47 Tuc models computed with the Cluster Monte Carlo code (CMC). The models include all relevant dynamical interactions coupled to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 108 publications
(177 reference statements)
0
11
0
Order By: Relevance
“…These clusters are of particular interest because they lie in front of the rich stellar backgrounds of the SMC and the Galactic bulge, respectively. We base our microlensing rate estimates for these GCs on our models of 47 Tuc (Ye et al 2021) and M22 (Kremer et al 2019) that best match these clusters' observed surface brightness and velocity dispersion profiles, as determined by the χ 2 fitting methodology described by Kremer et al (2019) and Rui et al (2021a).…”
Section: Tuc and M22mentioning
confidence: 99%
See 2 more Smart Citations
“…These clusters are of particular interest because they lie in front of the rich stellar backgrounds of the SMC and the Galactic bulge, respectively. We base our microlensing rate estimates for these GCs on our models of 47 Tuc (Ye et al 2021) and M22 (Kremer et al 2019) that best match these clusters' observed surface brightness and velocity dispersion profiles, as determined by the χ 2 fitting methodology described by Kremer et al (2019) and Rui et al (2021a).…”
Section: Tuc and M22mentioning
confidence: 99%
“…To match 47 Tuc, Ye et al (2021) vary the initial number of stars, density profile, binary fraction, virial radius, tidal radius, and IMF. The density profile of the bestfitting model is an Elson profile (Elson et al 1987) with γ = 2.1.…”
Section: Tuc and M22mentioning
confidence: 99%
See 1 more Smart Citation
“…It is now routine to create entire grids of 𝑁-body star cluster models with > 10 6 stars and binaries covering a realistic range of initial conditions that can reproduce GCs and other massive star clusters in the local universe. But while this approach has had great success creating models of individual star clusters in the MW (e.g., van der Marel et al 1997;Hurley et al 2001;Baumgardt et al 2003;Heggie & Giersz 2014;Heggie 2014;Wang et al 2016a;Kremer et al 2018;Ye et al 2021), near every study of galactic and extra-galactic GC systems has started from idealized grids of initial conditions designed only to reproduce MW GCs. While this method allows us to create one-to-one mappings between individual MW clusters and 𝑁-body models (e.g., Baumgardt & Hilker 2018;Weatherford et al 2020;Rui et al 2021b), it neglects the wealth of information that cosmological models of star cluster formation can provide, such as the cluster initial mass function (CIMF), initial radii, metallicities, ages, galactic tidal fields, and more.…”
Section: Introductionmentioning
confidence: 99%
“…The high densities within the centers of core-collapsed clusters lead naturally to an increased rate of close stellar encounters of these objects, and therefore, an increased rate of stellar collisions and tidal disruptions (e.g., Heggie & Hut 2003). A number of studies have shown that close tidal interactions involving specifically neutron stars and stars may lead to the formation of compact binaries (e.g., Fabian et al 1975;Ray et al 1987;Ivanova et al 2005;Ye et al 2021). Even closer encounters inevitably lead to collisions of neutron stars and stars (e.g., Krolik et al 1984;Rasio & Shapiro 1991;Lombardi et al 2006;Perets et al 2016;Kremer et al 2019b).…”
mentioning
confidence: 99%